Effectiveness of two didactic methods on child’s attitude for preserving their oral health - Gutiérrez Ilave, Margot (2007)
It was determined the effect on the attitude for preserving the buccal health of male and female children of 8 and 9 year old; with two didactic methods, one based on game of rules nominated DENTOPLAY and the other, expositive method for an expert using scale models and posters. There were 8 sessions, one per week, each one lasted 45 minutes, the topics were similar for both groups. It was established the attitude for three components, cognitive (knowledge and believes) with four indicators, accessibility, importance and maintenance of the buccal health, dental decay; affective about nutritious preferences, self care, dentist’s image, motivation, self confidence, spokesman of buccal health in family environment; and the volitional one conformed by participation, attention and children’s concentration. The Oral Hygiene was evaluated before and after the experience. The results showed that both didactic methods allow increasing the degree of knowledge and information. The Game of Rules, Dentoplay, didactive method distributed the affective component in positive intensity, while the Expositive one in a half intensity. The Kendall Test, probe a positive correlation in the game of rules group, in all volitional variables including the Oral Hygiene control; with a higher attention-concentration lineal relationship (0.84), p <0.05. The U Mann-Whitney test showed a significant difference in volitional variables when comparing both didactic methods.